Benign cardiac schwannoma: A case report - Serge Koujanian, MD; Bernard Pawlowicz, MD; David Landry, MD, FRCPC; Iakovina Alexopoulou, MD, FRCPC; Vidhya Nair, MD, FRCPC (Human Pathology: Case Reports, 2017)
We present an interesting case of a 47-year-old female with an incidental finding of a cardiac tumor located between the right atrium and right ventricle. After some time, the patient became symptomatic, the mass was excised, and pathological studies revealed it to be a benign schwannoma. Schwannomas are tumors of nerve sheaths commonly found in cranial and peripheral nerves. Their occurrence in the heart is exceedingly rare. Keywords: Cardiac, Tumor, Schwannoma